Urgensi Psikologi Kriminil Dalam Penanganan Kejahatan Jalanan - Hetharia, Zefanya Fernioren; Hehanussa,, Deassy Jacomina Anthoneta; Wadjo, Hadibah Zachra (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2023)
Introduction: Criminal psychology investigates individual behavior, particularly the causes of criminal behavior. Purposes of the Research: Analyze and explain the Urgency of Criminal Psychology in handling street crime. Methods of the Research: This study uses the Juridical Empirical Legal Research method. Sources of data used are primary data, secondary data, and tertiary data by collecting data through filling out questionnaires, interview methods and literature study and then analyzed based on the theoretical concept approach. Results Originality of the Research: The findings of this study demonstrate that by understanding the life of criminal psychology, crime as human behavior can be avoided because criminal psychology is the primary psychological basis for criminals, the causes of crime, and prevention, both preventive and repressive as repair or healing efforts. By taking into account psychological and personal factors as well as the reasons people commit crimes, this can also be strengthened by minimizing and accommodating the factors that lead to someone committing street crimes in order to meet limited needs.